Coupled eco-hydrology and biogeochemistry algorithms enable the simulation of water table depth effects on boreal peatland net CO.sub.2 exchange - Mezbahuddin, Mohammad; Grant, Robert F; Flanagan, Lawrence B (Biogeosciences, 2017)
Water table depth (WTD) effects on net ecosystem CO.sub.2 exchange of boreal peatlands are largely mediated by hydrological effects on peat biogeochemistry and the ecophysiology of peatland vegetation. The lack of representation of these effects in carbon models currently limits our predictive capacity for changes in boreal peatland carbon deposits under potential future drier and warmer climates. We examined whether a process-level coupling of a prognostic WTD with (1) oxygen transport, which controls energy yields from microbial and root oxidation-reduction reactions, and (2) vascular and nonvascular plant water relations could explain mechanisms that control variations in net CO.sub.2 exchange of a boreal fen under contrasting WTD conditions, i.e.,Â shallow vs.Â deep WTD. Such coupling of eco-hydrology and biogeochemistry algorithms in a process-based ecosystem model, ecosys, was tested against net ecosystem CO.sub.2 exchange measurements in a western Canadian boreal fen peatland over a period of drier-weather-driven gradual WTD drawdown. A May-October WTD drawdown of â¼ 0.25 m from 2004 to 2009 hastened oxygen transport to microbial and root surfaces, enabling greater microbial and root energy yields and peat and litter decomposition, which raised modeled ecosystem respiration (R.sub.e) by 0.26 Âµmol CO.sub.2 m.sup.-2 s.sup.-1 per 0.1 m of WTD drawdown. It also augmented nutrient mineralization, and hence root nutrient availability and uptake, which resulted in improved leaf nutrient (nitrogen) status that facilitated carboxylation and raised modeled vascular gross primary productivity (GPP) and plant growth. The increase in modeled vascular GPP exceeded declines in modeled nonvascular (moss) GPP due to greater shading from increased vascular plant growth and moss drying from near-surface peat desiccation, thereby causing a net increase in modeled growing season GPP by 0.39 Âµmol CO.sub.2 m.sup.-2 s.sup.-1 per 0.1 m of WTD drawdown. Similar increases in GPP and R.sub.e caused no significant WTD effects on modeled seasonal and interannual variations in net ecosystem productivity (NEP). These modeled trends were corroborated well by eddy covariance measured hourly net CO.sub.2 fluxes (modeled vs.Â measured: R.sup.2 â¼ 0.8, slopes â¼ 1 Â± 0.1, intercepts â¼ 0.05 Âµmol m.sup.-2 s.sup.-1 ), hourly measured automated chamber net CO.sub.2 fluxes (modeled vs.Â measured: R.sup.2 â¼ 0.7, slopes â¼ 1 Â± 0.1, intercepts â¼ 0.4 Âµmol m.sup.-2 s.sup.-1 ), and other biometric and laboratory measurements. Modeled drainage as an analog for WTD drawdown induced by climate-change-driven drying showed that this boreal peatland would switch from a large carbon sink (NEP â¼ 160 g C m.sup.-2 yr.sup.-1) to carbon neutrality (NEP â¼ 10 g C m.sup.-2 yr.sup.-1) should the water table deepen by a further â¼ 0.5 m. This decline in projected NEP indicated that a further WTD drawdown at this fen would eventually lead to a decline in GPP due to water limitation. Therefore, representing the effects of interactions among hydrology, biogeochemistry and plant physiological ecology on ecosystem carbon, water, and nutrient cycling in global carbon models would improve our predictive capacity for changes in boreal peatland carbon sequestration under changing climates.